"Cut her some slack": examining twenty-first century ecofeminist digital opinion leader #AOC and the #GreenNewDeal - Clemmons, Zoe Eileen, author; Arthur, Tori Omega, advisor; Anderson, Karrin, committee member; Champ, Joseph, committee member (Colorado State University. Libraries, 2020)
Alexandria Ocasio-Cortez holds a unique and captivating spot in the political arena in 2020. At the forefront of the nonbinding resolution, the Green New Deal (GND), her position on Twitter with over 6.7 million followers has given her the power to influence and interact with her constituents, other politicians, supporters, and critics on Twitter and has given her the opportunity to advocate for and uphold key policy issues related to environmental justice within the Green New Deal. She can also shape policy decisions as the Green New Deal moves forward. Ecofeminism, as both a social and philosophical movement, argues that women must be at the forefront of politics in order to improve the lives of others and the environment. Employing Critical Technocultural Discourse Analysis (CTDA) to understand digital phenomena, artifacts, and ideology on social networking platforms, this study explores how and why Alexandria Ocasio-Cortez as a twenty-first century opinion-leader generates support for the Green New Deal, and how she uses ecofeminism as a principle that guides her Green New Deal advocacy on Twitter. This thesis offers an overview of the study, its theoretical frames, methodology, findings, and discussion.
Cut her some slack: examining twenty-first century ecofeminist digital opinion leader #AOC and the #GreenNewDeal
Keywords: ecofeminism; Twitter; environmental justice; CTDA; opinion leaders; Green New Deal